Recapitulation of Werner syndrome sensitivity to camptothecin by limited knockdown of the WRN helicase/exonuclease - Bird, J; Jennert-Burston, K; Bachler, M; Mason, P; Lowe, J; Heo, S; Campisi, J; Faragher, R; Cox, L (2012)
WRN is a RecQ helicase with an associated exonuclease activity important in DNA metabolism, including DNA replication, repair and recombination. In humans, deficiencies in WRN function cause the segmental progeroid Werner syndrome (WS), in which patients show premature onset of many hallmarks of normal human ageing. At the cellular level, WRN loss results in rapid replicative senescence, chromosomal instability and sensitivity to various DNA damaging agents including the topoisomerase inhibitor, camptothecin (CPT). Here, we investigate the potential of using either transient or stable WRN knockdown as a means of sensitising cells to CPT. We show that targeting WRN mRNA for degradation by either RNAi or hammerhead ribozyme catalysis renders human fibroblasts as sensitive to CPT as fibroblasts derived from WS patients, and furthermore, we find altered cell cycle transit and nucleolar destabilisation in these cells following CPT treatment. Such WS-like phenotypes are observed despite very limited decreases in total WRN protein, suggesting that levels of WRN protein are rate-limiting for the cellular response to camptothecin. These findings have major implications for development of anti-WRN agents that may be useful in sensitising tumour cells to clinically relevant topoisomerase inhibitors. © 2011 Springer Science+Business Media B.V.